Competing epistemologies in the construction of popular science - Davis, Pryce (2018)
This paper focuses on how the personal epistemologies of scientists and science communicators shape their practices and interact with one another in the construction of popular science news. I present data from observations and interviews with scientists and reporters as they work together to produce science news to show how competing epistemologies result in compromises that—when presented to the public—might lead readers to form understandings that are at odds with disciplinary knowledge.